Absorption spectra and mechanical properties of C : F nanocoatings deposited from laser plasma onto leucosapphire surface. (1st April 2022) - Sergeev, P.B.; Kravchuk, K.S.; Morozov, N.V.
Abstract: It is experimentally shown that during laser annealing of micron layers of fluorocarbon oil by high-power KrF laser radiation pulses, C : F nanocoatings with a thickness of up to ∼100 nm can be synthesised on a leucosapphire surface. The absorption spectra of these coatings, measured in the 0.19 – 6 μm range, virtually coincided with the absorption spectra of fluorographene in the quantum energy range of 5 ± 1 eV. The nanohardness and elasticity modulus of the C : F nanocoatings are found to be 7 and 250 GPa, respectively, which is close to the characteristics of fluorographene.